The effect of microeconomic factors on the performance of islamic bank - evidence from Malaysia / Nurul Atiqah Amirah Norhak - Norhak, Nurul Atiqah Amirah (2019)
Malaysia is one of countries that implemented dual banking systems. The developing of Islamic banking system has made Malaysia become one of the most important hubs in the world. This study aims to examine the factors that will significantly affect the Islamic banks’ performance. This study utilizes the secondary data collected from the yearly financial reports of 7 Islamic banks in Malaysia from 2010 to 2017. The explanatory variables are categorized into internal factors in this study. The internal factors include capital adequacy, bank size and operational efficiency. From the result, it is found that capital adequacy and operational efficiency have significant impact on the profitability Islamic banks. It is worth to mention that operational efficiency is the only factor that brings the same effect to the profitability in Islamic banks, which is significant positive effect.